Minimum wages, globalization and poverty in Honduras - T. H. Gindling; Katherine Terrell (Institute for the Study of Labor (IZA), 2006)
To be competitive in the global economy, some argue that Latin American countries need to reduce or eliminate labor market regulations such as minimum wage legislation because they constrain job creation and hence increase poverty. On the other hand, minimum wage increases can have a direct positive impact on family income and may therefore help to reduce poverty. We take advantage of a complex minimum wage system in a poor country that has been exposed to the forces of globalization to test whether minimum wages are an effective poverty reduction tool in this environment. We find that minimum wage increases in Honduras reduce extreme poverty, with an elasticity of -0.18, and all poverty, with an elasticity of -0.10 (using the national poverty lines). These results are driven entirely by the effect on workers in large private sector firms, where minimum wage legislation is enforced. Increases in the minimum do not affect the incidence of poverty in sectors where minimum wages are not enforced (small firms) or do not apply (self-employed and public sector).
urn:nbn:de:101:1-20080509172
Keywords: 330; Mindestlohn; Armut; Honduras